Seroprevalence of Rubella Among Pregnant Women in Relation with Sociodemographic Change in Sylhet Region of Bangladesh (Journal of Monno Medical College, 2026)
Background: Clinical or subclinical infection of rubella in pregnant women can give rise to congenital rubella infection of her baby.Objectives: The purpose of the study was to see the prevalence of rubella virus specific IgG antibody among pregnant women.Methodology: This cross-sectional study was conducted in the Department of Microbiology in collaboration with the Department of Obstetrics & Gynaecology at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh during the period from January to December 2019 for a duration of one year. By simple random sampling pregnant women with the age between 16 to 38 years attending antenatal clinic were selected according to inclusion and exclusion criteria. Anti-rubella antibody (IgG) titre was measured by Enzyme-Linked Immunosorbent Assay (ELISA) method.Results: A total number of 207 individuals were included in this study. Among them 186(89.9%) participants had protective immunity and 21(10.1%) participants had no protective immunity against rubella. Protective immunity was higher in age group 26-30 years and then it was declined as age increases (p=0.042). Protective immunity was found in 61 (82.43%) participants of 1st trimester, 64 (94.12%) participants of 2nd trimester and 61(93.85%) participants of 3rd trimester(p=0.031). Protective immunity was in 103 (90.35%) urban participants and 83 (89.25%) in rural participants (p=0.794). Protective immunity was found in 70 (93.33%) participants of lower class, 97 (90.65%) participants of middle class, 19 (76%) participants of higher class (p=0.042).Conclusion: In conclusion, the substantial percentage of pregnant women are susceptible for rubella infection.  Journal of Monno Medical College, June, 2025; 11(1) : 60-64